FDI and the digital economy: The need for policy alignment - Xavier Forneris (Columbia University, Columbia Center on Sustainable Investment (CCSI), 2025)
Many countries want to move toward the "digital economy," an arduous journey that can be facilitated by FDI's catalytic power. This Perspective suggests that countries should make sure that their promotion, incentive and entry policies are aligned to this strategic objective and it provides concrete examples of what such alignment means.
Keywords: 330